THE PURCHASE POWER OF THE COMMUNITY AND GOVERNMENT SUBSIDIES ON MSME PRODUCTION PERFORMANCE IN THE COVID-19 PANDEMIC - Prasetio Ariwibowo; Bakti Toni Endaryono (Universitas Semarang, 2021)
This study was conducted to find out how much influence the purchasing power of the people and government subsidies have in maintaining the existence of MSME entrepreneurs during the Covid-19 pandemic which has been running for almost 2 years. The total sample of this research is 100 MSME entrepreneurs in Jakarta and Bogor Regency by purposive sampling who are engaged in the food and beverage sector. Descriptive quantitative method with analytical test tools using SEM-PLS 3.0. with the analysis technique carried out, namely descriptive analysis, inferential analysis, validity test, reliability test, R-square test, T-test and F-test. The results of data analysis obtained in this study are that in the middle of the condition of people's purchasing power, it simultaneously affects performance. MSME production and subsidies from the government have no simultaneous effect on MSME revenue performance during the Covid-19 pandemic. Simultaneously, brand image and price affect purchasing decisions.Penelitian ini dilakukan untuk mengetahui seberapa besar pengaruh kekuatan daya beli masyarakat dan subsidi pemerintah dalam mempertahankan eksistensi pengusaha UMKM di masa pandemi Covid-19 yang sudah berjalan selama hampir 2 tahun, khususnya di bidang pendapatan usaha. Total sampel dari penelitian ini adalah 100 pengusaha UMKM di Jakarta dan Kabupaten Bogor secara purposive sampling yang bergerak di sektor makanan dan minuman. Metode kuantitatif deskriptif dengan alat uji analisis menggunakan SEM-PLS 3.0. dengan teknik analisis yang dilakukan yaitu analisis deskriptif, analisis inferensial, Uji validitas, Uji Reliabilitas, Uji R-Square, Uji -T dan Uji F. Hasil analisis data yang diperoleh pada penelitian ini yaitu di tengah kondisi daya beli masyarakat berpengaruh secara simultan terhadap kinerja produksi UMKM dan subsidi dari pemerintah tidak berpengaruh secara simultan terhadap kinerja pendapatan UMKM di masa pandemi di masa Covid-19. Secara simultan, citra merek dan harga berpengaruh terhadap keputusan pembelian